Analysis of Accounting Information Systems for Raw Materials and Finished Goods: Analisis Sistem Informasi Akuntansi Persediaan Bahan Baku dan Barang Jadi - Novitasari, Maya; Maryanti, Eny (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze the Accounting Information System for Raw Materials and Finished Goods at PT Berkat Ganda Sentosa Pasuruan. The research approach used is the qualitative approach. The research method used is descriptive method. The data collection method used interview, documentation and observation. The interview method was used to seek in-depth information by asking questions to the company staff and academic experts. The documentation method is carried out to support and strengthen the data in research. The observation method is carried out to record information and activities that occur during field research. In this research, using data analysis techniques such as data reduction, data presentation and data verification. The results of this study indicate that the Raw Material Inventory Accounting Information System at PT. Berkat Ganda Sentosa, this is done well but is still manual, with procedures starting from purchasing to receiving inventory, purchase returns, demand and release of warehouse goods, use of raw materials and also physical inventory counts. All these procedures are carried out with the aim that the mutation of raw material inventory can be controlled easily which consists of various functions with their respective duties and responsibilities along with the completeness of documents that can be accounted for. The structure of the implementation of an Accounting Information System for raw material inventory of PT Berkat Ganda Sentosa Pasuruan includes functions related to AIS, documents and records used as well as a network of procedures that can form an Accounting Information System.